“Girl, You Are a New Species of Krazy” - Selina Linda Mudavanhu (Communicare)
On 18 April 2016, Dr Stella Nyanzi, then, a researcher at the Makerere Institute of Social Research (MISR) stripped in protest against being evicted from her office by Professor Mahmood Mamdani, Director of MISR. The conflict that had been brewing for years between the two was primarily around Nyanzi’s refusal to teach on the PhD programme at MISR. Though Nyanzi had people endorsing her choice of protest, others criticised her. Drawing on the Othering theory, this paper examines the ways in which criticisms to Dr Nyanzi’s protest were represented on YouTube. First, Nyanzi was framed on the social media platform as mad. Second, Nyanzi was regarded as having contravened behaviour expected of ‘educated people.’ Third, her stripping was framed as unholy and unAfrican. Fourth, Nyanzi’s undressing was labelled criminal. Nyanzi’s othering served to discredit her protest. Many of Nyanzi’s critics neglected to engage with the issues that she raised.